Spare parts procurement planning at KM Trans Logistics - Roy, Debjit; Bandyopadhyay, Arindam (London : SAGE Publications Ltd, 2017)
It was a clear and sunny winter morning of February 2014 in Gidani. However, the people in the office of the Executive Director of workshop operations, KM Trans Logistics India Pvt. Ltd, were in a somber mood. Anuj and Arihant Jain, the Executive Directors in-charge, were discussing fresh problem created by store managers of the workshops in Gidani and Gurgaon. The problem was disorderly procurement of spare parts (for repair and maintenance of trucks) by store managers. Every few days, adhoc purchase orders were raised for vendors in batch quantities of 50 or 100.
Originally published: Roy, D., & Bandyopadhyay, A. (2014). Spare parts procurement planning at KM Trans Logistics. PROD0298. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; KM Trans Logistics; Automobile supplies industry -- India -- Case studies; Trucks -- Parts -- Case studies